Pendekatan Game Android Untuk Meningkatkan Minat Belajar Matematika Siswa Sekolah Dasar - Moh. Syadidul Itqan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
Every people being is getting accustomed to using android based smartphone, not exception elementary school students. Even parents feel the hassle when asked his son to learn if using a smartphone. Therefore a new approach is needed in order for the elementary school students easily asked learning. One such approach is to use an android based smartphone as a media students learning. The method of this research is research and development method. System development used is waterfall. The purpose of this research resulted in the android game to increase interest in learning. The result of this research is android based games have been produced to increase interest in learning mathematics elementary school students. Keywords: Game, Android, Interest in Learning